Temporal changes in radiocesium deposition in various forest stands following the Fukushima Dai-ichi Nuclear Power Plant accident. (January 2017) - Kato, Hiroaki; Onda, Yuichi; Hisadome, Keigo; Loffredo, Nicolas; Kawamori, Ayumi
Abstract: In this study, we investigated the transfer of canopy-intercepted radiocesium to the forest floor following the Fukushima Dai-ichi Nuclear Power Plant accident. The 137 Cs content of throughfall, stemflow, and litterfall were monitored in two coniferous stands (plantations of Japanese cedar) and a deciduous mixed broad-leaved forest stand (oak with red pine) from July 2011 to December 2012. The forest floor of cedar stands had received higher levels of additional 137 Cs deposition compared with the mixed broad-leaved stand during the sampling period. The cumulative 137 Cs deposition during the study period was 119 kBq m −2 for the mature cedar stand, 105 kBq m −2 for the young cedar stand, and 41.5 kBq m −2 for the broad-leaved stand. The deposition of 137 Cs to the forest floor occurred mainly in throughfall during the first rainy season, from July to September 2011 (<200 d after the initial fallout); thereafter, the transfer of 137 Cs from the canopy to forest floor occurred mainly through litterfall. A double exponential field-loss model, which was used to simulate the removal of 137 Cs from canopies, was the best fit for the temporal changes in the canopy 137 Cs inventory. Highlights: We investigated transfer of canopy-intercepted radiocesium to the forest floor. Coniferous cedar stands showed greater initial canopy interception. Coniferous stands showed greater 137 Cs deposition than the deciduous stand. Double exponential model was useful for determining canopy 137 Cs content. Litterfall effectively accelerate 137 Cs transfer from canopy to forest floor.